2023
DOI: 10.3389/fpubh.2023.1074272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atropine 0.01% on myopia control in children aged 6–13 years during the 2022 lockdown in Shanghai

Abstract: PurposeTo compare the myopic progression in children treated with 0. 01% atropine and those who discontinued atropine during the 2022-home quarantine in Shanghai.MethodsIn this retrospective study, children aged 6–13 years with follow-up visits before (between January 2022 and February 2022) and after the lockdown (between July 2022 and August 2022) were included. Cycloplegic refraction and axial length (AL) were measured at both visits. The atropine group had continuous medication during the lockdown while th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Of the 13 studies, two studies ( Erdinest et al, 2022b ; Erdinest et al, 2023 ) explored combination therapy with atropine. The 8 RCTs ( Tong et al, 2009 ; Chia et al, 2016 ; Zhu et al, 2020 ; Yam et al, 2022a ; Ye et al, 2022 ; Hieda et al, 2023 ; Medghal et al, 2023 ; Wei et al, 2023 ) and 5 non-RCTs ( Lin et al, 2013 ; Polling et al, 2020 ; Erdinest et al, 2022b ; Erdinest et al, 2023 ; Yu et al, 2023 ) included 2,060 children under 18 years old, and 9 of the studies were conducted in Asian countries, including Singapore and China. The average age of participants was 10.3 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 studies, two studies ( Erdinest et al, 2022b ; Erdinest et al, 2023 ) explored combination therapy with atropine. The 8 RCTs ( Tong et al, 2009 ; Chia et al, 2016 ; Zhu et al, 2020 ; Yam et al, 2022a ; Ye et al, 2022 ; Hieda et al, 2023 ; Medghal et al, 2023 ; Wei et al, 2023 ) and 5 non-RCTs ( Lin et al, 2013 ; Polling et al, 2020 ; Erdinest et al, 2022b ; Erdinest et al, 2023 ; Yu et al, 2023 ) included 2,060 children under 18 years old, and 9 of the studies were conducted in Asian countries, including Singapore and China. The average age of participants was 10.3 years old.…”
Section: Resultsmentioning
confidence: 99%
“…The follow-up time reported for participants was between 5 and 24mo. The specific characteristics are presented in Table 1 [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . Risk of Bias Eight studies mentioned the use of a table of random numbers to generate a randomized sequence, 8 studies mentioned the use of blinding of researchers during intervention implementation and outcome measurement, 10 studies described in detail the rate and reason behind loss of sample, and 14 studies had essentially balanced baseline information between the experimental and observation groups before intervention.…”
Section: Resultsmentioning
confidence: 99%
“…The Optimal Atropine Concentration in Terms of Efficacy and Safety A total of 14 articles [19][20][21][22][23][24][25][26][27][28][29][30][31][32] , of which 11 were RCTs, and three were retrospective cohort studies, were included to assess the efficacy of 1%, 0.05%, 0.025%, 0.02%, and 0.01% atropine for the treatment of Chinese children and adolescents using network Meta-analysis as an evaluation tool to select the optimal concentration for clinical provision. The results of this study showed that five different concentrations of atropine solution were superior to the control group in terms of efficacy.…”
Section: Discussionmentioning
confidence: 99%